(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Financial literacy is an essential life skill for adolescents, particularly vocational school students who are preparing to enter employment, continue their studies, or develop small business initiatives. This community service activity addressed the limited practical understanding of allowance management, saving habits, and emergency fund planning among twelfth-grade students of SMKN 1 Takari, Kupang Regency. The activity was conducted on Thursday, April 9, 2026, involving 30 students. An educational-participatory approach was applied through interactive lectures, guided discussion, allowance-management simulation, budgeting worksheets, and final reflection. The materials covered financial literacy, the distinction between needs and wants, spending priorities, simple expense recording, saving strategies, and emergency fund planning. The evaluation was based on facilitator observation, question-and-answer responses, worksheet review, and participant reflection. The results showed that all participants were involved in the simulation and worksheet activities. The most dominant achievements were participants’ ability to identify daily spending patterns, classify needs and wants, prepare simple allowance budgets, and formulate realistic plans to set aside small amounts for savings and emergency purposes. The activity strengthened students’ awareness that allowance is not merely for consumption but can become a learning medium for responsible financial behavior. The program provides a practical model for strengthening adolescent financial life skills in vocational school settings.